Implementation of Kurikulum Merdeka in IPS Learning by IPS Teachers at SMP Negeri 2 Semparuk, Kecamatan Semparuk, Kabupaten Sambas - Alya Istiqla Zuvita; Mashudi Mashudi; Hadi Wiyono; Iwan Ramadhan (JURNAL PENDIDIKAN IPS, 2024)
This study aims to determine the Implementation of IPS learning in the Kurikulum Merdeka by Social Studies Teachers at SMP Negeri 2 Semparuk, Kabupaten Sambas. This research uses a qualitative method with a descriptive form. Data collection in this study used non-participant observation techniques, interview techniques, then documentation techniques. Sources of data used using primary and secondary data sources with 2 social studies teachers, principals, vice principals, and 4 students. Data analysis techniques used using techniques according to Miles and Huberman, namely data reduction, data presentation, and conclusion drawing. Test the validity of the data in this study using triangulation techniques and sources. The results of this study found that: 1) IPS learning planning for the Kurikulum Merdeka by social studies teachers at SMP Negeri 2 Semparuk is reviewing various regulations, understanding learning outcomes, developing learning outcomes into a flow of learning objectives, developing a flow of learning objectives into teaching modules. 2) The implementation of the Kurkulum Merdeka in IPS learning carried out by IPS teachers at SMP Negeri 2 Semparuk is the implementation of initial assessment, learning using modules, social studies learning, formative and summative assessment/evaluation, and the advantages of Kurikulum Merdekan in IPS learning. 3) The obstacles faced by IPS teachers in IPS learning with using Kurikulum Merdeka are difficulties in understanding the Learning Outcomes, difficulties in developing teaching modules, and difficulties in understanding the initial assessment of learning.